Whitefly Infestation and Economic Comparison of Two Different Pest Control Methods on Soybean Production - Fitrah Murgianto; Purnama Hidayat (Universitas Muhammadiyah Yogyakarta, 2017)
Insecticide application is a common practice done by farmers to control the whitefly Bemisia tabaci. While the use of insecticide can suppress the whitefly population, the cost of soybean production is also increased. The objective of this research was to compare the whitefly infestation and economic of two whitefly control methods on soybean production.Two sets of experiments were done, one set with insecticide application and another one without insecticide application. Ten soybean cultivars were used in each set of experiment with completely randomized design and three replications.The whitefly infestation was observed weekly on sample plants on each plot. The benefit and R/C ratio were calculated based on revenue and total costs of soybean production. The average whitefly (egg and nymphs) population on the plots with insecticide application was 4.95 for egg and 5.72 for nymph per leaf, which was lower than those without insecticide application 11.76 for egg and 10.86 for nymph per leaf. The average benefit and R/C ratio for the plots with insecticide application were IDR 9,654,507/ha and 1.51 respectively, while the average benefit and R/C ratio for the plots without insecticide application were IDR 8,706,299/ha and 1.55 respectively. The study can be concluded thatgrowing soybean without insecticide treatmentwas more efficient than growing soybean with insecticide applications